Peran Self-Compassion dalam Menurunkan Tingkat Academic Burnout Pada Mahasiswa Indonesia - Afrizawati Afrizawati; Nur Zahrani (Psychopolytan : Jurnal Psikologi, 2025)
Social skills are an essential component of life skills that support students' academic success and emotional development. Guidance and counseling play a strategic role in helping students develop these skills through services that foster empathy, effective communication, and social cooperation. This study aims to examine whether guidance and counseling significantly influence students' social skills at SMK Hang Nadim Batam. The study involved 95 students selected using a simple random sampling technique. The instruments used were a social skills scale and a guidance and counseling scale. The social skills scale consisted of 20 items with a reliability coefficient of α = 0.836, while the guidance and counseling scale also consisted of 20 items with α = 0.932. The hypothesis testing results showed a significance value (Sig) of 0.000, which is less than the probability threshold of 0.05. Thus, the null hypothesis (Ho) is rejected, and the alternative hypothesis (H₁) is supported, indicating that guidance and counseling have a statistically significant impact on students' social skills at SMK Hang Nadim Batam. The coefficient of determination (R Square) was 0.300, meaning that guidance and counseling contribute 30% to the development of students’ social skills. Therefore, the findings of this study highlight the importance of optimizing school guidance and counseling programs as an effective and sustainable means to enhance students' social skills.